Professional and public accreditation as an assessment of agricultural educational program quality in Russia / Natalya A. Medvedeva, Nikolay G. Malkov and Marina L. Prozorova - A. Medvedeva, Natalya; G. Malkov, Nikolay; L. Prozorova, Marina (Universiti Teknologi MARA, 2021)
The aim of the study is to substantiate methodological approaches to the agricultural educational program development on the basis of a modular-competence-based approach, which provides training for the experts of the agricultural industry, capable of implementing a federal scientific and technical program in the future for the development of agriculture in Russia, taking into account the requirements of professional standards. Professional and public accreditation of agricultural educational programs will allow for an external examination of the educational program implementation level and quality in accordance with approved professional standards and develop recommendations aimed at student training level improvement. The study defines the role of professional and public accreditation provision in the interaction between the labor market and the vocational education system. The authors substantiated the modular-competence-based approach to the development of educational programs that contributes to human capital quality improvement in agriculture. In this paper, an algorithm has been developed to expert training quality improvement.In general, the result of the work will contribute to the training of personnel for the industry and will ensure the achievement of a balance of qualifications between the labor market and agricultural education.